Rekonstruksi Hukum Kewarisan Islam Kontemporer dalam Perspektif Maqāṣid al-Syarī‘ah: Kajian atas Penundaan Pembagian Warisan, Pemerataan Hak Waris, dan Hibah Pra-Wafat di Indonesia - Putri Melani; Heri Firmansyah (Tabayyun : Journal Of Islamic Studies, 2026)
Contemporary Islamic inheritance law encounters various challenges resulting from social change, evolving notions of justice, and increasingly complex family property relations. In Indonesia, the postponement of inheritance distribution, the equalization of inheritance rights, and the use of inter vivos gifts (hibah) prior to death frequently raise legal debates because they appear to conflict with the normative framework of farā’iḍ. This study aims to reconstruct contemporary Islamic inheritance law through the perspective of maqāṣid al-sharī‘ah by examining these three issues within the context of Indonesian Islamic law. This research employs a normative legal method using statutory, conceptual, and analytical approaches. The study relies on primary legal sources, including the Qur’an, Hadith, and the Compilation of Islamic Law (KHI), as well as secondary sources from classical and contemporary Islamic legal scholarship. The findings indicate that postponement of inheritance distribution is permissible when justified by legitimate interests and does not prejudice the rights of heirs. Equalization of inheritance rights may be accommodated through consensual mechanisms such as ṣulḥ and at-takharruj after heirs understand their respective legal shares, as reflected in Article 183 KHI. Likewise, hibah may serve as a lawful instrument of wealth distribution and estate planning, provided that it is not used to undermine the inheritance rights of other heirs. Article 211 KHI functions as a corrective mechanism to ensure fairness in such circumstances. The study concludes that the reconstruction of contemporary Islamic inheritance law requires the integration of farā’iḍ, Islamic legal flexibility, Indonesian positive law, and the objectives of maqāṣid al-sharī‘ah in order to achieve justice, legal certainty, family harmony, and public welfare.